Innovative Process Development in Metallurgical Industry Concept to Commission - Lakshmanan, Vaikuntam Iyer; Roy, Raja; Ramachandran, V. (Springer International Publishing : Imprint: Springer, 2016)
This book describes the phases for innovative metallurgical process development, from concept to commercialization. Key features of the book include: • Need for process innovation • Selection and optimization of process steps • Determination of the commercial feasibility of a process including engineering and equipment selection • Determination of the environmental footprint of a process • Case-study examples of innovative process development .